The Effect of Secondary Metabolism Content in Plant Leaves on Mung Bean Seed Germination - Mina Arinta Putri; Firman Ali Rahman; Muhammad Yul Fikry; Mai Rizali; Muamar Kadafin (Yayasan Tajuk Indonesia, 2024)
Secondary metabolites are a class of compounds contained in the bodies of microorganisms, flora and fauna which are formed from primary metabolic processes. The aim of this research is to determine the effect of metabolism in plants on the germination process of green beans. The method used is a qualitative method with a descriptive analysis research approach, data collection using observation and documentation. The results of observations made in the provision of different water, where the green beans treated with well water grew very quickly, the green beans treated with cassava leaf water grew quite well, while the green beans treated with papaya water and guava leaf water grew slowly.